Changes in cancer mortality rates after Medicaid expansion under the Affordable Care Act and the role of changes in stage at diagnosis. Issue 28 (1st October 2022) - Barnes, Justin Michael; Johnson, Kimberly J.; Osazuwa-Peters, Nosayaba; Chino, Fumiko
Abstract : 74 Background: Medicaid expansion is associated with earlier cancer diagnoses and improved cancer survival. However, it is unclear if the expansion-associated survival benefits are driven primarily by early detection leading to improved prognosis and/or increased access to appropriate cancer care. A nationwide analysis was performed to determine the degree to which expansion-associated changes in cancer mortality rates can be explained by changes in stage at diagnosis. Methods: State-level cancer incidence and mortality data from 2001-2019 for individuals ages 20-64 years were obtained from the combined Surveillance, Epidemiology, and End Results and National Program of Cancer Registries databases (incidence) and the National Center for Health Statistics (mortality), which cover the 50 US States and Washington DC. Difference-in-differences analyses were conducted to compare changes in localized and distant stage cancer incidence rates and cancer mortality rates from pre- vs. post-2014 in expansion vs. non-expansion states. We utilized generalized estimating equations to account for autocorrelation within states and adjusted for age, race, sex, year, state, early Medicaid expansion effects, and state-level covariates (unemployment, education, poverty, race/ethnicity, and insurance). Analyses were conducted overall and by cancer site subtype. Mediation analyses were utilized to assess whether local and/or distant stage diagnosis rates were mediators of the changes in cancer mortality rates. Results: The data consisted of 16, 470 state-year observations stratified by age, sex and race. In our adjusted analyses with all cancer sites combined, there were decreases in the distant stage cancer incidence rate (OR: 0.966, 95% CI = 0.942 - 0.991, P =.009) and cancer mortality rate (OR: 0.974, 95% CI = 0.950 - 0.999, P =.041) after Medicaid expansion in expansion relative to non-expansion states. There were no expansion-associated changes in localized cancer incidence rates (OR: 0.989, P =.45). Changes in distant stage cancer incidence mediated 26% of the expansion-associated change in cancer mortality ( P =.013). By cancer site, there were Medicaid expansion-associated decreases in cancer mortality rates for breast (OR: 0.954, P <.001), cervical (OR: 0.934, P =.020), and colorectal (OR: 0.945, P =.045) cancers, though local or distant stage incidence rates were not found to be statistically significant mediators. Conclusions: Medicaid expansion was associated with decreased metastatic stage cancer incidence and decreased overall cancer mortality. Approximately 25% of the improvements in cancer mortality can be attributed to decreases in metastatic diagnoses suggesting increased rates of curative-intent treatment, amongst other factors. Remaining survival benefits may reflect access to timely, quality cancer care not captured in this analysis.